Sentencing and the iron cage: judges’ experiences with rationalization - Smith, Justin M. (Journal of crime and justice, 2019)
Judicial decision-making has significant consequences for individuals, families, local communities, and social institutions. Mandatory sentencing guidelines were originally created to control disparity in the sentencing process. After years of implementation, they further embedded rationalization in the system, which has formalized complex processes leading to mass incarceration. However, recent court cases have made guidelines advisory rather than mandatory in some states. The purpose of this study is to examine Michigan judges’ experiences with sentencing guidelines one year after shifting from mandatory to advisory guidelines, and to examine how guidelines constrain and enable discretion in judicial decision-making. It draws upon theories of the rationalization of criminal justice organizations and past research on criminal courts. Our results show (1) guidelines serve as an influential ‘starting point,’ and frame sentencing decisions, (2) formal and substantive rationality both continue to influence sentencing, and (3) judges perceive the shift to advisory guidelines will only have minimal effects on sentencing patterns across the state.